Application, purification, and recovery of ionic liquids - Kuzmina, Olga; Hallett, Jason P. (Elsevier, 2016)
Application, Purification, and Recovery of Ionic Liquids provides a comprehensive overview of the usage of ionic liquids (IL). The book gives a description of the methods used for recovery and purification of ILs, a summary of the economic aspects of using ILs, and a review on the toxicity data of ILs. It is written for researchers, scientists, and engineers working with ILs, their properties, and usages. The book not only describes the chemical aspects, but the economic and environmental aspects as well, making it of particular interest to professionals applying this technology.